Analysis of Students' Collaborative, Communication, Critical Thinking, and Creative Abilities through Problem-Based Learning - Susetyarini, Eko; Nurohman, Endrik; Husamah, H. (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
Students' collaborative, critical thinking, creative thinking, and communication skills need to be trained using problem-based learning on sharing and jumping tasks, which has never been studied. This study aimed to analyze students' collaborative, communication, critical, and creative thinking skills using Problem-Based Learning (PBL). This type of research is descriptive. The research design uses a Lesson Study-based case study. The population in this study were all 5th-semester students who attended lectures on Human and Animal Anatomy Physiology at the Biology Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Malang, the Academic year 2021/2022. The sample of this study was students of class 5C with 38 people (total sampling). Data were collected by observation by eight observers using an assessment rubric. Aspects that are measured include critical thinking, creative, collaborative, and communication skills through descriptive quantitative data analysis with percentages. The results showed that students' collaborative, critical thinking, creative thinking, and communication skills were in the good category. There was an increase in the first and second cycles through problem-based learning. The findings of this study are problem-solving-oriented learning can improve classical 4C skills.